2019
DOI: 10.1016/j.nicl.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional abnormalities on MRI in kabuki syndrome

Abstract: Kabuki syndrome (KS) is a rare congenital disorder (1/32000 births) characterized by distinctive facial features, intellectual disability, short stature, and dermatoglyphic and skeletal abnormalities. In the last decade, mutations in KMT2D and KDM6A were identified as a major cause of kabuki syndrome. Although genetic abnormalities have been highlighted in KS, brain abnormalities have been little explored. Here, we have investigated brain abnormalities in 6 patients with KS (4 males; Mage = 10.96 years, SD = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
(31 reference statements)
2
13
1
Order By: Relevance
“…Cedrik et al reported two patients presented with holoprosencephaly [21]. Furthermore, based on MRI, significantly decreased grey matter volume in the bilateral hippocampus and dentate gyrus have been described in KS patients [22]. We found the brain abnormalities including thinning of pituitary and myelination of cerebral white matter in Chinese KS patients, which were not previously reported in KS patients.…”
Section: Discussionsupporting
confidence: 45%
“…Cedrik et al reported two patients presented with holoprosencephaly [21]. Furthermore, based on MRI, significantly decreased grey matter volume in the bilateral hippocampus and dentate gyrus have been described in KS patients [22]. We found the brain abnormalities including thinning of pituitary and myelination of cerebral white matter in Chinese KS patients, which were not previously reported in KS patients.…”
Section: Discussionsupporting
confidence: 45%
“…Among the major structural brain anomalies in KS patients, Dandy-Walker malformations have been reported in three patients [ 22 , 28 , 29 ]. In addition to major anomalies, based on MRI, Jennifer et al found that the volume of gray matter in the bilateral hippocampus and dentate gyrus in patients with KS was significantly decreased compared those in healthy controls [ 30 ]. MRI of our patient showed cystic enlargement of the fourth ventricle and hypoplasia of the cerebellar vermis, which fulfilled the diagnostic criteria of Dandy-Walker variant.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…We previously described a mouse model of KS1, Kmt2d +/βgeo [Mll2Gt(RRt024)Byg], demonstrating characteristic features including craniofacial abnormalities and visuospatial memory impairments, associated with decreased adult-born hippocampal NSPCs in the dentate gyrus (DG) (12). Decreased DG gray matter volume was subsequently observed in patients with KS1 (13). The continual birth and integration Chromatin modifiers act to coordinate gene expression changes critical to neuronal differentiation from neural stem/progenitor cells (NSPCs).…”
Section: Introductionmentioning
confidence: 99%